Roles of P-body factors in Candida albicans filamentation and stress response. - Melissa A Tosiano; Frederick Lanni; Aaron P Mitchell; C Joel McManus (PLoS Genetics)
Hyphal growth is strongly associated with virulence in the human fungal pathogen Candida albicans. While hyphal transcriptional networks have been the subject of intense study, relatively little is known about post-transcriptional regulation. Previous work reported that P-Body (PB) factors Dhh1 and Edc3 were required for C. albicans virulence and filamentation, suggesting an essential role for post-transcriptional regulation of these processes. However, the molecular roles of these factors have not been determined. To further study the function of PB factors in filamentation, we generated homozygous deletions of DHH1 and EDC3 in diverse prototrophic clinical strains using transient CRISPR-Cas9. Homozygous DHH1 deletion strongly impaired growth, altered filamentation, and exhibited unusual colony morphology in response to heat stress in five strain backgrounds. Using RNA-seq, we found DHH1 deletion disrupts the regulation of thousands of genes under both yeast and hyphal growth conditions in SC5314 and P57055. This included upregulation of many stress response genes in the absence of external stress, similar to deletion of the S. cerevisiae DHH1 homolog. In contrast, we found EDC3 was not required for heat tolerance or filamentation in diverse strains. These results support a model in which DHH1, but not EDC3, represses hyphal stress response transcripts in yeast and remodels the transcriptome during filamentation. Our work supports distinct requirements for specific mRNA decay factors, bolstering evidence for post-transcriptional regulation of filamentation in C. albicans.